Analisis Kadar Albumin Pra dan Post Hemodialisa pada Penderita Gagal Ginjal Kronik - Seri Rayani Bangun; Elisa Putri Nadapdap; Rica Vera Br Tarigan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Chronic renal failure (CKD) is a progressive decline in kidney function so that it cannot maintain hemostasis in the body, in order to maintain hemostasis in the body, hemodialysis is carried out in patients with kidney failure, to replace kidney function. Examination of albumin is serum or plasma taken from venous blood. The purpose of this study was to analyze albumin levels in patients with chronic renal failure pre and post hemodialysis at Santa Elisabeth Hospital Medan. This research method is descriptive. The population in this study were 178 patients with a total sample of 64 respondents. The method used to examine albumin levels is Bromocresol Green (BCG). The results showed that pre-hemodialysis albumin levels in patients with chronic renal failure had an average of 3.080. g/dL. Post-hemodialysis albumin levels have an average of 3.683 g/dL. Based on the examination of albumin levels in patients with chronic renal failure pre and post hemodialysis, it was found that albumin levels had increased within normal limits. Thus, patients with chronic kidney failure undergoing hemodialysis check their blood albumin levels to avoid hypoalbumin and routinely consult nutrition.